1993
DOI: 10.1177/109019819302000110
|View full text |Cite
|
Sign up to set email alerts
|

Coping with Rheumatoid Arthritis: Is One Problem the Same as Another?

Abstract: This study examined how individuals with rheumatoid arthritis (RA) cope with illness-related problems in four different areas: daily activities, leisure activities, work, and social relationships. Eighty-five people with RA took part in the study. They participated in an in-depth interview that focused on the types of changes they had experienced in their lives as a result of their arthritis and how they had coped with these changes. Audiotapes of the interviews were transcribed and content analyzed to assess … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
38
0
6

Year Published

1994
1994
2007
2007

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 56 publications
(47 citation statements)
references
References 27 publications
3
38
0
6
Order By: Relevance
“…This consistency of self-management strategies across stressors contrasts with some other studies. For example, Tack (39) noted that patients reported different coping behaviors for fatigue than for other problems, and Blalock et al (8) noted little consistency in use of coping strategies for problems with daily activities, leisure activities, work, and social relationships (although Blalock et al did find that individuals were more likely to use behavioral strategies to cope with problems with functioning, i.e., daily activities, leisure activities, and work, than to cope with problems with social relationships). Previous assessments of coping have categorized coping into a variety of styles, such as active versus passive coping; problem-focused versus emotion-focused coping; and optimistic cognitions, self-control, and behavioral coping (10,19,40 -42).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This consistency of self-management strategies across stressors contrasts with some other studies. For example, Tack (39) noted that patients reported different coping behaviors for fatigue than for other problems, and Blalock et al (8) noted little consistency in use of coping strategies for problems with daily activities, leisure activities, work, and social relationships (although Blalock et al did find that individuals were more likely to use behavioral strategies to cope with problems with functioning, i.e., daily activities, leisure activities, and work, than to cope with problems with social relationships). Previous assessments of coping have categorized coping into a variety of styles, such as active versus passive coping; problem-focused versus emotion-focused coping; and optimistic cognitions, self-control, and behavioral coping (10,19,40 -42).…”
Section: Discussionmentioning
confidence: 99%
“…Self-management behaviors would appear to fall within this definition of coping. For example, Blalock and colleagues (8) identified a number of behavioral coping strategies for problems with daily and leisure activities, work, and social relationships that might be construed as self-management behaviors, including modification (changing something about a situation or behavior), perseverance (attempting to continue despite problems), and material resources (using special equipment or devices). Two scales used to assess coping with pain, the Coping Strategies Questionnaire (9) and the Vanderbilt Pain Management Inventory (10), assess specific behaviors in addition to emotions and cognitions used to cope with pain, and van Lankveld and colleagues include behaviors in their Coping with Rheumatic Stressors scale (11).…”
Section: Introductionmentioning
confidence: 99%
“…Blalock et al (27) have taken this approach. Patients were interviewed regarding how they coped with various aspects of their disease.…”
Section: Issues Of Methodology and Theorymentioning
confidence: 99%
“…Blalock and colleagues (27) suggest that flexibility in coping may be crucial to the maintenance of well-being in the face of disease activity. They found that arthritis patients who used the greatest number of different coping strategies had higher scores on tests of psychological well-being.…”
Section: Approaches To Coping-distress Relationshipsmentioning
confidence: 99%
“…Although no researcher has been able to identify the "best" coping strategy, strategies in which the individual tries to function in spite of pain are usually related to better psychological and physical functioning, whereas passive strategies like restricting activities or relying on others are linked to greater pain and emotional distress (Turk & Monarch, 2002). Further, since there is no ultimate way to cope, effective stress management may be more about flexibility, whereby a greater diversity of pain coping strategies seems to be associated with better psychological adjustment in patients with chronic pain (Blalock, DeVellis, Holt & Hahn, 1993;Haythornthwaite, Menefee, Heinberg & Clark, 1998).…”
Section: Copingmentioning
confidence: 99%